Intercultural Education for Multicultural Society - Mesić, Milan, sociolog (Array, 2008)
This paper presents some basic arguments in favor of intercultural dialogue through education. Intercultural education aims to provide for the kind of knowledge, attitudes, and skills needed today's young people to function within different cultures in their own society. Students who can relate positively to and function within a variety of cultures in their own nation are also more likely to orientate themselves successfully in cultures in other nations than are individuals who view domestic ethnic cultures as exotic and strange.